Mutually Dependent: Power, Trust, Affect and the Use of Deception in Negotiation - Olekalns, Mara (Journal of business ethics, 2009)
Using a simulated two-party negotiation, we examined how trustworthiness and power balance affected deception. In order to trigger deception, we used an issue that had no value for one of the two parties. We found that high cognitive trust increased deception whereas high affective trust decreased deception. Negotiators who expressed anxiety also used more deception whereas those who expressed optimism also used less deception. The nature of the negotiating relationship (mutuality and level of dependence) interacted with trust and negotiators’ affect to influence levels of deception. Deception was most likely to occur when negotiators reported low trust or expressed negative emotions in the context of nonmutual or low dependence relationships. In these relationships, emotions that signaled certainty were associated with misrepresentation whereas emotions that signaled uncertainty were associated with concealment of information. Negotiators who expressed positive emotions in the context of a nonmutual or high dependence relationship also used less deception. Our results are consistent with a fair trade model in which negotiator increases deception when contextual and interpersonal cues heighten concerns about exploitation and decrease deception when these cues attenuate concerns about exploitation.